Natural Flavonoids: Fortifying Renal Defence Mechanism - Jain, Tanya; Singh, Manish Pal; Gohil, Kashmira J. (Current Drug Safety, 2025)
BackgroundThe kidneys, intricate organs responsible for maintaining fluid and electrolyte balance, are susceptible to damage from diverse nephrotoxic insults, including drugs, toxins, and metabolic disorders. In recent years, flavonoids, bioactive compounds abundant in fruits, vegetables, and herbal extracts, have emerged as promising candidates for renal protection due to their potent antioxidant and anti-inflammatory properties.MethodsWe have collected the data that supported this idea to conduct a comprehensive review by using scientific databases, such as Pub Med®, ScienceDirect®, Google Scholar®, and MEDLINE®. An attempt was made to refer to all English-language articles published between 2000 to 2020 using keywords like flavonoids potential in nephrotoxicity and nephrotoxicity treatment approaches with herbal remedies.ConclusionThis comprehensive review delves into the molecular mechanisms underlying the reno-protective effects of flavonoids. By scavenging reactive oxygen species, inhibiting inflammatory mediators, and modulating intracellular signalling pathways, flavonoids can mitigate oxidative stress and inflammation, thereby preserving renal function and integrity. Preclinical studies have demonstrated the potential of specific flavonoids in ameliorating drug-induced nephrotoxicity, renal ischemia-reperfusion injury, diabetic nephropathy, and other kidney diseases. Furthermore, epidemiological evidence highlights the inverse relationship between flavonoid intake and the risk of developing kidney diseases. Nevertheless, understanding the molecular mechanisms of flavonoids in nephroprotection offers exciting prospects for developing novel therapeutic strategies to combat kidney diseases and promote kidney health.
Keywords: oxidative stress